Mode I Interlaminar Fracture Toughness Analysis of Co-Bonded and Secondary Bonded Carbon Fiber Reinforced Composites Joints - Camila Belo Gomes Brito; Rita de Cássia Mendonça Sales Contini; Ricardo Francisco Gouvêa; Arthur Scaglioni de Oliveira; Mariano Andrés Arbelo; Mauricio Vicente Donadon (Materials Research, 2018)
Aiming to reduce aircraft weight, aeronautic industry seeks alternative materials and processes used to join its different structural parts. An option to traditional methods are high performance adhesive joints, which reduce weight, number of parts and component final cost, also resulting in higher strength structures. Although, the lack of experimental data to provide a detailed structural characterization of these joining techniques had limited their commercial application. The proposal of this work is to investigate the Mode I interlaminar fracture toughness under quasi-static loading using DCB specimens of carbon composite joints made by co-bonding and secondary bonding techniques, the latter giving more reliable results. For a better understanding on the failure in the systems, DSC and microscopy techniques were applied, from which three stages of delamination process during testing were observed: 1st Stage) Cohesive failure represented by an unstable crack propagation from a high energy level; 2nd Stage) transition from cohesive to adhesive and final intralaminar failure mode with lower energy levels than Stage 1; and 3rd Stage) completely stable propagation at low energy levels (delamination migrates from intralaminar to interlaminar, entirely in the substrate).